Vegetation cover induces developmental plasticity of lateralization in tadpoles. Issue 4 (5th December 2019) - Lucon-Xiccato, Tyrone; Dadda, Marco; Bisazza, Angelo
Abstract: Lateralization of cognitive functions influences a large number of fitness-related behaviors and shows, in most species, substantial variation in strength and direction. Laboratory works and field data have suggested that this variation is often due to adaptive phenotypic plasticity. Strong lateralization should be favored in some ecological conditions, for example, under high risk of predation. For anuran tadpoles, the presence of cover affects predation risk, with tadpoles being more exposed to predators in environments with reduced cover. We tested the hypothesis that the amount of cover experienced early in life affects lateralization in the edible frog, Pelophylax esculentus, tadpoles. We exposed embryos and larvae to high or low vegetation cover environments. For half of the subjects, the treatment was constant whereas the remaining subjects were switched to the opposite treatment after hatching. In agreement with the theoretical expectation, tadpoles exposed to low vegetation cover for the entire development were more lateralized and showed a stronger alignment in directionality of lateralization compared with tadpoles exposed to high vegetation cover. This indicates a possible role of natural variation in vegetation abundance and developmental plasticity as determinants of between-population and between-individual differences in lateralization. We also found that shifting from high to low vegetation cover treatments and vice versa disrupted lateralization alignment, suggesting that developmental trajectories for this trait are determined at the embryonic stage and need environmental stability to be fully expressed.